ANALISIS PENGARUH BUDAYA ORGANISASI, LOCUS OF CONTROL TERHADAP KINERJA APARAT PEMERINTAH DAERAH DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Pemerintah Kabupaten Bengkalis) - Endang Sri Wahyuni; Rosmida Rosmida (Politeknik Negeri Bengkalis, 2017)
Abstract: This purpose of this study is to examine the effect of organizational culture, locus of control, on the performance of district governments. This study also examine the mediating role of job satisfaction effect on organizational culture, locus of control, on the performance of district governments. The population in this study are all of SKPD Bengkalis District Government and purposive sampling is used as sampling method. This study uses questioner for 183 respondents. The analysis technique used is the technique of path analysis using SPSS version 17.0. The results showed prove that organizational culture affect on the performance of district governments, locus of control affect on the performance of district governments. Job satisfaction variable as mediating the effect of organizational culture on the performance of district governments, Job satisfaction variable as mediating the effect of locus of control on the performance of district governments. Keywords: Performance, District, Goverment, Organizational, Culture, Locus of Control (LOC), Job Satisfaction.